Predictive model of intention to pursue higher education: the integration of subjective well-being, resilience, and self-efficacy in Central Kalimantan - Munandar, Haris; Guntoro, Dibyo Waskito (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2024)
This research aims to predict the relationship between subjective well-being, resilience, and self-efficacy on the intention to pursue higher education in Central Kalimantan, addressing a research gap in this region. It employed the theory of planned behavior. The research used a quantitative correlational method with psychological scales as instruments. The sample consisted of 319 twelfth-grade high school students. Results indicated that all three variables successfully predicted the intention to pursue higher education, with resilience making the largest contribution (44.9%). These findings improve our understanding of the psychological factors influencing the intention to pursue higher education in Central Kalimantan